Associations between catecholaminergic, GABAergic, and serotonergic genes and self-reported attentional function in oncology patients and their family caregivers. Issue 3 (June 2015) - Merriman, John D.; Aouizerat, Bradley E.; Cataldo, Janine K.; Dunn, Laura B.; Kober, Kord; Langford, Dale J.; West, Claudia; Cooper, Bruce A.; Paul, Steven M.; Miaskowski, Christine
Abstract Purpose of the research Evaluate for associations between variations in genes involved in catecholaminergic, gamma-aminobutyric acid (GABA)-ergic, and serotonergic mechanisms of neurotransmission and attentional function latent classes. Patients and methods This descriptive, longitudinal study was conducted at two radiation therapy departments. The sample included three latent classes of individuals with distinct trajectories of self-reported attentional function during radiation therapy, who were previously identified using growth mixture modeling among 167 oncology patients and 85 of their family caregivers. Multivariable models were used to evaluate for genotypic associations of neurotransmission genes with attentional function latent class membership, after controlling for covariates. Results Variations in catecholaminergic (i.e., ADRA1D rs4815675, SLC6A3 rs37022), GABAergic (i.e., SLC6A1 rs2697138), and serotonergic (i.e., HTR2A rs2296972, rs9534496) neurotransmission genes were significant predictors of latent class membership in multivariable models. Conclusions Findings suggest that variations in genes that encode for three distinct but related neurotransmission systems are involved in alterations in attentional function. Knowledge of both phenotypic and genetic markers associated with alterations in attentional function can be used by clinicians to identify patients and family caregivers who are at higher risk for this symptom. Increased understanding of the genetic markers associated with alterations in attentional function may provide insights into the underlying mechanisms for this significant clinical problem.